2012
DOI: 10.5897/ajb12.201
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sowing date on the growth and yield of maize cultivars (Zea mays L.) and the growth temperature requirements

Abstract: A field experiment was conducted to analyze the relationship between growing degree days, yield and yield components of maize cultivars. Five maize cultivars (SC 108, SC 301, SC 604, SC 704 and TVG) were sown on four different dates during summer in a randomized complete block design with split plot arrangements with three replications. Maize cultivars exhibited significant differences on yield, weight of 100 seeds, biological yield and harvest index. The best hybrid SC 704 accumulated growing degree days (GDD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 4 publications
1
17
0
Order By: Relevance
“…The SD3 had higher cumulative Srad and CHU compared to SD1 and SD2; however, the cumulative precipitation amount received during SD3 was lower compared to SD1 and SD2 and this could have contributed to lower grain yield. The GDDs decreased with delay in SD and this study agrees with the findings of Dahmardeh (2012).…”
Section: Effect Of Sowing Date On Growing Degree Days Crop Heat Unitsupporting
confidence: 91%
“…The SD3 had higher cumulative Srad and CHU compared to SD1 and SD2; however, the cumulative precipitation amount received during SD3 was lower compared to SD1 and SD2 and this could have contributed to lower grain yield. The GDDs decreased with delay in SD and this study agrees with the findings of Dahmardeh (2012).…”
Section: Effect Of Sowing Date On Growing Degree Days Crop Heat Unitsupporting
confidence: 91%
“…Seed weights are components of yield where its contribution strongly influenced by the environment (Johnson et al, 1996). In this connection, significant effect of sowing time on HSW where the higher HSW was produced by early sown maize plants also documented by Dahmardeh (2012). Similarly, Pettigrew (2002) reported that early planted cotton recorded higher lint (about 8%), number of bolls m -2 and lint percentage significantly than did cotton in the normal planting.…”
Section: Treatmentsmentioning
confidence: 58%
“…Delayed sowing (6 July) increased fresh ear yield and fresh kernel yield compared with 5 June in 2010 and 2011, respectively. Dahmardeh (2012) reported that seed yields generally increased with later planting dates with the lowest yield from the earliest planting date. Low yields from the first and second sowing dates were likely associated with the detrimental effects of high temperatures and low humidity on pollination, fertilization, and grain filling.…”
Section: Resultsmentioning
confidence: 99%